Amplitude death and restoration in networks of oscillators with random-walk diffusion - Pau Clusella (Nature Portfolio, 2021)
Since Turing’s seminal work, combining local reaction with diffusion is key to understand how patterns can appear in interacting systems. Here, the authors investigate the effect of coupling local dynamics with a non-traditional type of diffusion mechanism, random-walk diffusion, showing that this simple modification can give rise to previously unobserved amplitude death and restoration of collective oscillations